2018
DOI: 10.3390/app8060871
|View full text |Cite
|
Sign up to set email alerts
|

A State-of-the-Art Review of Nanoparticles Application in Petroleum with a Focus on Enhanced Oil Recovery

Abstract: Research on nanotechnology application in the oil and gas industry has been growing rapidly in the past decade, as evidenced by the number of scientific articles published in the field. With oil and gas reserves harder to find, access, and produce, the pursuit of more game-changing technologies that can address the challenges of the industry has stimulated this growth. Nanotechnology has the potential to revolutionize the petroleum industry both upstream and downstream, including exploration, drilling, product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
132
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(140 citation statements)
references
References 170 publications
(249 reference statements)
0
132
0
8
Order By: Relevance
“…Recently, nanoparticles are proposed as a possible additive in fluids used in the oil and gas industry based on their ripping characteristics of particle size, large area/volume ratio, and so on, allowing a better transfer of mass and energy . Regarding conformance control with polymer gel systems, Lakatos et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanoparticles are proposed as a possible additive in fluids used in the oil and gas industry based on their ripping characteristics of particle size, large area/volume ratio, and so on, allowing a better transfer of mass and energy . Regarding conformance control with polymer gel systems, Lakatos et al .…”
Section: Introductionmentioning
confidence: 99%
“…The study of Zhang et al (2011) pointed out the benefit of NPs surface coating tailored to achieve certain additional properties that could withstand the effect of high temperature. Agista et al (2018) also provide a comprehensive review on the state of the art of NPs application in EOR. The authors summarized different functionalized NPs, particularly SiO 2 NPs, to achieve various influential factors in nano-stabilized foam.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have conducted core flooding studies and demonstrated the potential of silica NPs to increase oil recovery [2,[10][11][12][13][14][15][16]. Adsorption and transport of nanoparticles in porous media is of primary importance for subsurface applications as this determines the effectiveness of the nanofluid injection.…”
Section: Introductionmentioning
confidence: 99%